Self-referential encoding does not benefit memory for prior remembering across changing contexts. Issue 9 (21st October 2021) - Leppanen, Marcus L.; Navangul, Anaya S.; Feder, Gabriella I.; Jones, Dominoe A.; Kim, Kyungmi
ABSTRACT: Changes in context across instances of memory retrieval have been shown to impair memory for acts of prior remembering. The present study examined how self-referential encoding influences memory for prior remembering that occurred with or without context change. At encoding, participants processed each target in cue-target word pairs in relation to themselves or another person. During an initial cued-recall test, targets were tested with either the studied cues or semantically related, but previously unseen cues. During a second cued-recall test, all targets were tested with the studied cues, and participants judged whether they remembered retrieving each target during the first test. Regardless of self/other-reference, semantic context change across the two tests impaired memory for prior remembering. Furthermore, the magnitude of this impairment was larger for strongly self-associated vs. other-associated targets. Our findings suggest that self-referential encoding does not benefit memory for prior remembering in the face of contextual change.